2011
DOI: 10.1111/j.1473-4192.2010.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Metalinguistic explanations and self‐reports as triangulation data for interpreting second language sociolinguistic performance

Abstract: The study reported here explores the use of learners' metalinguistic explanations and self‐reports of variable language production as triangulation data for interpreting second language (L2) sociolinguistic performance, focusing on the variable retention versus omission of the negative morpheme ne. Our central argument is that performance data alone are not sufficient for evaluating how L2 learners perceive social and stylistic variation in the language they are studying. To this end, an analysis of data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The development of sociolinguistic competence by advanced second language (L2) learners is an area of interest within the field of SLA that has come under increased research-based scrutiny over the last decade or two (e.g., Bayley & Preston, 1996; Bayley & Regan, 2004; Dewaele & Regan, 2001; Geeslin, 2000; Iwasaki, 2008; Killam, 2011; Li, 2010; R. Mougeon, Nadasdi, & Rehner, 2010; Schmidt, 2011; van Compernolle, 2011). This research has focused on the sociolinguistic competence of learners of different second or foreign languages (e.g., Chinese, English, French, Japanese, or Spanish) from a variety of linguistic backgrounds.…”
mentioning
confidence: 99%
“…The development of sociolinguistic competence by advanced second language (L2) learners is an area of interest within the field of SLA that has come under increased research-based scrutiny over the last decade or two (e.g., Bayley & Preston, 1996; Bayley & Regan, 2004; Dewaele & Regan, 2001; Geeslin, 2000; Iwasaki, 2008; Killam, 2011; Li, 2010; R. Mougeon, Nadasdi, & Rehner, 2010; Schmidt, 2011; van Compernolle, 2011). This research has focused on the sociolinguistic competence of learners of different second or foreign languages (e.g., Chinese, English, French, Japanese, or Spanish) from a variety of linguistic backgrounds.…”
mentioning
confidence: 99%
“…What seems less clear is the impact the IC has on learner performance from an ontogenetic perspective. As van Compernolle and Williams (2011) have noted, although this type of pedagogical intervention has a clear positive effect on developing learners' understanding of language variation, their productive use of variation does not develop at the same time or at the same speed. However, while conceptual understanding does not necessarily equate to performance abilities (Valsiner, 2001), 'it plays a critical role in guiding development of performance ability because it serves to orient learners to the meaning-making possibilities offered by the language' (Negueruela & Lantolf, 2006, p. 88).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, a cursory review of the chat data revealed a great deal of variation in the use of the second-person pronouns tu (T) and vous (V), inasmuch as many learners used one or the other of these pronouns indiscriminately, sometimes switching from T to V (or vice versa) within the same turn (see also McCourt, 2009;Williams, 2003). The intervention aimed to raise learners' awareness and understanding of sociolinguistic variation in French, in the hopes that their performance would also improve ( van Compernolle & Williams, 2011). The intervention consisted of a set of language analysis tasks focusing on the variable use of the pronouns tu 'you-informal', vous 'you-plural' or 'you-singular-formal', nous 'we', and on 'one' or 'we', as well as the variable use of the negative morpheme ne, in a number of different discourse situations:…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…They include contradictory views across and within NSs, such as reported in Dubiner et al () and evidenced in the contradictory results of error‐gravity studies for German (DeLisle ; Politzer ), the differential between the idealized standard language taught in foreign language classrooms and the real‐life national and regional variants that, in turn, are bound by subtle social norms (e.g. Crispim ; Luzon, Campoy, del Mar Sanchez and Salazar ; Bieswanger ; Van Compernolle and Williams ), and the fact that communicative language teaching, the prevalent method of foreign language instruction in the US, has refrained from taking a firm ideological stance on accuracy, leaving matters of focus on form contested in both teaching practice and research (e.g. Basturkmen, Loewen, and Ellis ; Dyson ; Ellis, Basturkmen, and Loewen ).…”
Section: Limitations and Outlookmentioning
confidence: 98%